2011
DOI: 10.3791/2899
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Testing of Hypoxia in Cell Culture

Abstract: Hypoxia is defined as the reduction or lack of oxygen in organs, tissues, or cells. This decrease of oxygen tension can be due to a reduced supply in oxygen (causes include insufficient blood vessel network, defective blood vessel, and anemia) or to an increased consumption of oxygen relative to the supply (caused by a sudden higher cell proliferation rate). Hypoxia can be physiologic or pathologic such as in solid cancers [1][2][3] , rheumatoid arthritis, atherosclerosis etc… Each tissues and cells have a dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
195
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(201 citation statements)
references
References 9 publications
(1 reference statement)
4
195
0
2
Order By: Relevance
“…We demonstrated that CoCl 2 -induced hypoxia significantly increased metastases in both CCA cell lines, using a transwell migration assay. We also confirmed that CoCl 2 truly induces hypoxic conditions as demonstrated by the suppressing the protein level of PHD-2 and the increased level of hypoxia responsive elements HIF-1α and VEGF (Wu and Yotnda, 2011). In addition, we revealed that CoCl 2 -induced hypoxia facilitates CCA cells to metastasize by altering the level of proteins involved in EMT-mediated metastasis, i.e., reduction of E-cadherin to N-cadherin ratio, a hallmark of EMT (Gravdal et al, 2007;Chen et al, 2014) were observed for M139 and M214 cells.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We demonstrated that CoCl 2 -induced hypoxia significantly increased metastases in both CCA cell lines, using a transwell migration assay. We also confirmed that CoCl 2 truly induces hypoxic conditions as demonstrated by the suppressing the protein level of PHD-2 and the increased level of hypoxia responsive elements HIF-1α and VEGF (Wu and Yotnda, 2011). In addition, we revealed that CoCl 2 -induced hypoxia facilitates CCA cells to metastasize by altering the level of proteins involved in EMT-mediated metastasis, i.e., reduction of E-cadherin to N-cadherin ratio, a hallmark of EMT (Gravdal et al, 2007;Chen et al, 2014) were observed for M139 and M214 cells.…”
Section: Discussionsupporting
confidence: 64%
“…Under hypoxic conditions, the PHDs process is inhibited, theSuyanee Thongchot 1,3 , Watcharin Loilome 1,3 , Puangrat Yongvanit 1,3 , Hasaya Dokduang 1,3 , Raynoo Thanan 1,3 , Anchalee Techasen 2,3 , Nisana Namwat 1,3 * angiogenesis, and intracellular proteins which allow cells to survive in O 2 deprivation by reprogramming their metabolism (Semenza, 2012). Cobalt chloride (CoCl 2 ) is a chemically induced hypoxic-mimicking condition which occurs by inhibiting PHD and stabilizing HIF-1α, and it is frequently used for inducing a hypoxic condition in many in vitro systems (Yuan et al, 2003;Wu and Yotnda, 2011). It has been showed that 100 μM of CoCl 2 treatments to human prostate cancer cell lines resulted in elevated VEGF mRNA and protein secretion, and drove cells to be highly invasive metastatic phenotype (Liu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…3 In an attempt to mimic ischemia (hypoxia) and reperfusion (reoxygenation) in isolated renal PTE cells, we have pretreated the cells in media containing 200 mM CoCl 2 , reported to cause hypoxic conditions in various cell types in vitro. 18,19 After 24 hours' pretreatment, exchange of the media for oxygenated media containing no CoCl 2 resulted in a large transient increase in cellular calcium levels, while addition of ATP still produced a rapid calcium rise ( Figure 2D). The exchange of media without CoCl 2 pretreatment did not alter intracellular calcium levels (Supplemental Figure 2F).…”
Section: Gcamp2 Expression In Kidney Pt Cells: In Vitromentioning
confidence: 99%
“…Chemical hypoxia models that use mitochondrial uncoupling agents or respiration blockers reproduce the rapid onset of ischemia but there is no way to study the recovery processes that occur during reperfusion [6][7][8][9]. The significance of true hypoxia-reoxygenation models is in the capacity for recovery from the hypoxic phase, which makes these models especially useful for ischemia-related experiments.…”
Section: Introductionmentioning
confidence: 99%